Development of IT-Based Learning Media in English for Nurse Anesthetists - Dewi, Kadek Maya Cyntia; Suryati, Ni Wayan Novi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Education is the most important thing in life which is one of the platforms to deepen knowledge and hone skills. Education can be obtained through formal and informal learning. Education involves many people including learners (students), educators, administrators, parents and the community. Therefore, in order for educational goals to be achieved effectively and efficiently, everyone involved in it must understand the behavior of related individuals. The problem that is often faced in the world of education is the weak learning process. In the era of scientific and technological advances, of course, the world of education must keep up with the times. Because (Zubaidah & Sulistyaningrum, 2020). One of the efforts to improve the quality of learning outcomes is through improving teaching materials by using the right learning approach/model (Putra et al., 2017). (Putra et al., 2017). The challenges of world education in Electronic-based learning (Damuri et al., 2021) certainly require approaches related to educational problems in the form of questionnaires, questionnaires, interviews, and interactive learning media in digital form, but in reality students find it difficult to apply procedures for making learning media in the form of multimedia and besides that how they must be able to collaborate with the understanding of multimedia with the mathematics learning process so that in the learning process students easily understand (Supriyanto, 2020). The method used is research and development (R&D). Research has commercial interests in relation to pure scientific research and applicative development in the field of technology while development is the process of making, testing feasibility until revision. The subjects of this study were students in the D IV Anesthesiology Nursing study program in semester VI. They were selected by purposive sampling and the types of data taken were qualitative and quantitative. Data were collected through questionnaires and tests.